Ba Duan Jin Preliminary Analysis of the Second Type of Plantar Pressure. Issue 1 (22nd January 2018) - Ye, Jia; Sun, Dong; Fekete, Gusztáv
The mainly subject of this study was a common Ba Duan Jin (BDJ) practitioner. The plantar pressure distribution of nine distinct regions was analyzed during the execution of the one typical BDJ movements and Normal Walking (NK). The result of the experiment demonstrated that in BDJ movements, the pressure-time integral (PTI) of the 1st MTH was the maximum and greater than other parts in BDJ movements. The peak pressure (PP) of the 1st 2nd 3rd MTH and the GT were markedly greater than in other regions (p < 0.05). The center of pressure (COP) focused on the 1st 2nd 3rd MTH, and movement displacement is little. The result indicated that the 1st MTH plantar pressure of the second type of BDJ movement relative to NK a larger, to strengthen the 1st MTH and the GT region skin sensation, improving balance control. The plantar pressure distribution characteristics of BDJ movements found in this study may be one of the important factors that BDJ exercise improves elderly balance control.